PENGARUH PENDAPATAN BUNGA, UKURAN PERUSAHAAN DAN PRODUKTIVITAS TERHADAP RATING SUKUK - Dila Angraini (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
The purpose of this study was to examine the influence of the variable interest income, company size, and productivity on the corporate sukuk rating. The yield on the sukuk that will be received by investors illustrates the level of investor returns but the rate of return also describes the level of risk borne by investors. This research was conducted on all companies that issued sukuk which were listed on the Indonesia Stock Exchange for the period 2014-2018 and published their financial reports during the study period. The research sample is corporate sukuk with 35 data. This research was conducted using a quantitative approach with panel data. The data analysis technique used in this study was panel data regression with a random effect model. The results showed that interest income and productivity had no effect on the sukuk rating while firm size had an effect on the sukuk rating. This finding is in accordance with the existing theory that the factors that influence the corporate sukuk rating can be detected by the influence of non-financial variables.